Genetic diversity of human malaria parasites associated with continued malaria transmission in pre-elimination settings in South Africa - Birkholtz, Lyn-Marie (University of Pretoria, 2022)
Thesis (PhD (Biochemistry))--University of Pretoria, 2021.